2018
DOI: 10.1590/0103-8478cr20180596
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of endothelial cells from different regions of the cornea of dogs

Abstract: The aim of this study was to evaluate the morphology of endothelial cells from different areas of the cornea of dogs. Twenty healthy eyes from 10 dogs, females or males, of different ages were studied. Corneal endothelium morphology of superior, inferior, central, nasal and temporal areas was assessed by 0.2% alizarin red staining using an optic microscope. One hundred endothelial cells from each corneal area were analyzed. In all areas of the cornea studied were found endothelial cells with four sides, five s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…Corneal endothelial parameters have already been determined in some species, including humans ( Abib and Barreto, 2001 ), alligators ( Pigatto et al, 2004 ), ostriches ( Pigatto et al, 2009 ), chinchillas ( Bercht et al ., 2015 ), chickens ( Albuquerque et al ., 2015 ), rabbits ( Brambatti et al ., 2017 ), dogs ( Pigatto et al, 2006 ; Kobashigawa et al , 2015 ; Hünning et al ., 2018 ), sheep ( Brandao et al, 2006 ; Coyo et al, 2016 ) goats ( Coyo et al, 2018a , 2018b ), marmosets ( Morita and Shimomura, 1996 ), horses ( Andrew et al, 2001 ; Faganello et al ., 2016 ), owls ( Coyo et al, 2018a , 2018b ), llamas and alpacas ( Andrew et al, 2001 ), Magellan penguins ( Pigatto et al, 2005 ), and pigs ( Tamayo-Arango et al, 2009 ). However, there are few ophthalmological studies related to endothelial parameters in bovine species ( Tofflemire et al , 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corneal endothelial parameters have already been determined in some species, including humans ( Abib and Barreto, 2001 ), alligators ( Pigatto et al, 2004 ), ostriches ( Pigatto et al, 2009 ), chinchillas ( Bercht et al ., 2015 ), chickens ( Albuquerque et al ., 2015 ), rabbits ( Brambatti et al ., 2017 ), dogs ( Pigatto et al, 2006 ; Kobashigawa et al , 2015 ; Hünning et al ., 2018 ), sheep ( Brandao et al, 2006 ; Coyo et al, 2016 ) goats ( Coyo et al, 2018a , 2018b ), marmosets ( Morita and Shimomura, 1996 ), horses ( Andrew et al, 2001 ; Faganello et al ., 2016 ), owls ( Coyo et al, 2018a , 2018b ), llamas and alpacas ( Andrew et al, 2001 ), Magellan penguins ( Pigatto et al, 2005 ), and pigs ( Tamayo-Arango et al, 2009 ). However, there are few ophthalmological studies related to endothelial parameters in bovine species ( Tofflemire et al , 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the ECD and endothelial cell morphology were determined, and only parameters of the central area were analyzed. Although the peripheral regions were not analyzed in this study, previous studies found no significant difference in endothelial parameters when comparing peripheral regions with the central region ( Mccarey et al ., 2008 ; Bercht et al ., 2015 ; Faganello et al ., 2016 ; Brambatti et al ., 2017 ; Hünning et al ., 2018 ). Based on this, the data obtained in the central region can typically be extrapolated to the peripheral regions.…”
Section: Discussionmentioning
confidence: 99%
“…(TAKAHASHI et al, 1985). É possível observar no congelamento a -80°C o alto índice de células coradas e muitas células em que não era possível distinguir os limites celulares, visto que o VA cora com maior intensidade regiões com morte celular (HÜNNING et al, 2018). A avaliação histológica destacou danos em todas as camadas do tecido corneano nos tratamentos com os CPAs, corroborando com os resultados de viabilidade do endotélio e danos nas camadas epiteliais, sensíveis a possíveis efeitos de substância que entram em contato com essa camada (OLIVEIRA et al, 2015).…”
Section: Discussionunclassified